Preparation and Field Application of A Cellulose Triacetate–Based Optode for Cr(VI) Detection in Environmental Water Samples - Zulhan Arif; Fendy; Fransisca Gunawan; Elsa Febriani; Sri Sugiarti; Eti Rohaeti; Irmanida Batubara (Indonesian Scholar Society, 2025)
In this study, the optode was fabricated by incorporating 1,5-diphenylcarbazide and the ion carrier Aliquat 336 into a cellulose triacetate polymer matrix, which was subsequently modified using a dual-plasticizer system consisting of oleic acid and acetophenone. The successful synthesis of the optode was justified through FTIR spectroscopy to confirm functional group immobilization and screw micrometer measurements to ensure membrane thickness uniformity. A linear response was obtained within the concentration range of 0.02–0.40 ppm, with a determination coefficient (R²) of 0.9979, a limit of detection of 0.0108 ppm, a limit of quantitation of 0.0328 ppm, precision expressed as a relative standard deviation of 4.458%, and accuracy of 97.51%. The optode demonstrated high analytical sensitivity, as evidenced by a molar absorptivity of 2.262 × 10⁷ M⁻¹ cm⁻¹, along with excellent selectivity against common potentially interfering ions, including Fe(III), Pb(II), Zn(II), and Cd(II). The formed color complex exhibited good stability, remaining unchanged for up to five days. When applied to the determination of Cr(VI) in water samples, the optode yielded a concentration of 0.0664 ppm with satisfactory precision and accuracy. Although this value differed from the concentration obtained using UV–Vis spectrophotometry (0.0881 ppm), the overall performance of the optode was validated. Furthermore, a functional prototype was successfully developed and evaluated using real samples, producing favorable results. Collectively, these outcomes highlight the strong potential for further development and optimization of the proposed system.